COMPARATIVE STUDY OF THE EVOLUTION OF ATTENTIONAL ABILITIES IN TWO CLASSES FROM PRIMARY CYCLE IN WHICH CHESS IS STUDIED - Stegariu, V.I.; Abalașei, B.A.; Hakman, A.V.; Medvid, A.M. (ІННОВАЦІЙНА ПЕДАГОГІКА, 2022)
Chess is an extremely simple game because the general rules are well defined and during a tournament nobody can interfere in one’s game. Besides this, due to the fact that a game of chess is played under time pressure, he must evaluate the position precisely in a very short amount of time. Every cognitive skill required in a professional chess game likely transfers to other related fields where comprehension, analysis, memory, attention and evaluation of complex phenomena is required. Chess requires cognitive abilities and sophisticated problemsolving skills, thus providing a good opportunity to study the mechanisms underlying cognitive expertise. Researches have shown that during a chess game the frontal and posterior parietal area, which are specialized in orienting and maintaining attention, perception and short-term memory are used with predilection. Objective. The objective of this research is to highlight how chess practice influences the development of specific skills so much needed to improve the educational process. Methods of research. In this experiment we observed the level of attentional abilities of two classes in the primary cycle who study chess as an optional subject. The Kraepelin and Toulouse-Pieron tests were used to quantify the level of students in the two classes. These are the initial results that will be completed by the final ones before the end of the second semester. We tested 38 first grade students from a school in Iași County. They represent the collectives of two parallel classes that study chess as an optional subject for one hour each week. Both classes were evenly matched, 19 children each, but their composition differ. First class, named I A have 10 boys and 9 girls, meanwhile I D have 11 girls and 8 boys. Results. The results recorded by the two groups show similar values in both tests. We used the independent sample t-test to show that there are no statistically significant differences. The dispersion of the results within the groups presents the differences of the characters of the two collectives
ПОРІВНЯЛЬНЕ ДОСЛІДЖЕННЯ РОЗВИТКУ УВАГИ ДВОХ КЛАСІВ ПОЧАТКОВОЇ ШКОЛИ, З РОЗДІЛУ ПРОГРАМИ ШАХИ
Keywords: chess, children, attentional abilities